2013
DOI: 10.1002/adfm.201300255
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Synthesis of Mesoporous TiO2 Hollow Shells: Toward an Efficient Photocatalyst

Abstract: TiO 2 hollow shells with well-controlled crystallinity, phase, and porosity are desirable in many applications. In photocatalysis in particular, they can provide high active surface area, reduced diffusion resistance, and improved accessibility to reactants. Here, the results from studies of the causes for the failure of a prior etching and calcination scheme to make such shells and on a newly-developed simple yet robust process for producing uniform mesoporous TiO 2 shells with precisely controllable crystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
192
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 231 publications
(202 citation statements)
references
References 55 publications
7
192
0
Order By: Relevance
“…In addition to the intrinsic materials characteristics including low cost, low toxicity, and high chemical and optical stability [15,16], hollow nanostructures of TiO2 are believed to be able to provide a high active surface area, reduced diffusion resistance, and improved accessibility, which are beneficial features for photocatalysis. We have previously synthesized mesoporous hollow TiO2 shells with high surface areas through a surface-protected calcination process, revealed how the surface coating of another oxide or polymer could affect the crystallinity and the catalytic activity of the shells, and demonstrated that the phase composition, degree of crystallinity, surface area, and dispersity of TiO2 were important features required for photocatalysis [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the intrinsic materials characteristics including low cost, low toxicity, and high chemical and optical stability [15,16], hollow nanostructures of TiO2 are believed to be able to provide a high active surface area, reduced diffusion resistance, and improved accessibility, which are beneficial features for photocatalysis. We have previously synthesized mesoporous hollow TiO2 shells with high surface areas through a surface-protected calcination process, revealed how the surface coating of another oxide or polymer could affect the crystallinity and the catalytic activity of the shells, and demonstrated that the phase composition, degree of crystallinity, surface area, and dispersity of TiO2 were important features required for photocatalysis [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…[7][8] These materials have been explored in gas adsorption, [9] sensing, [10] catalysis, [11] as energy storagem aterials, [12] and in biological applications. [13] Aw ide range of organic transformations that involve bulky substrate molecules, such as the epoxide ring-opening reaction, [14] acid- [15] or base-catalyzed reactions, [16] photocatalysis, [17] ands ize-and shape-selective isomerization [18] are performed very efficiently over these materials with nanoscale porosity.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, a significant advancement in photocatalytic performance was obtained. Another key factor of a photocatalyst is its specific surface area, and scholars tend to synthesize mesoporous titania, [29][30][31][32][33] which thereby generates a larger reaction surface area and a stronger adsorption capacity. Metal or non-metal doping, [34][35][36] compositing, [37][38][39] hydrogenation, [40] and other means change mesoporous titania into a visible-light photocatalyst.…”
Section: Introductionmentioning
confidence: 99%